What mechanism design helps to realize the innovation function of maker-spaces: A qualitative comparative analysis based on fuzzy sets - Jiancun Zheng; Lu Shi; Tianhong Jiang (PloS one, 2022)
Most of the existing studies on maker-space focus on internal subjects (such as makers) or external factors (such as policy support, ecological environment, and more). There has been relatively little discussion on the design of a series of mechanisms of maker-space. This paper theorizes the operating mechanism for platform services, resource gathering, network connections and endogenous cultural protection for the maker-space. It uses the method of fuzzy set qualitative comparative analysis (fsQCA) to analyze data from 63 maker-spaces in Zhejiang Province. The study proposes a reasonable mechanism design scheme for maker-space. The results show that the innovativeness of a maker-space is the result of the synergistic effect of various operating mechanisms. Among them, the platform service function, the channel for gathering resources, the formal linkages, and the culture for sharing achievements are indispensable support mechanisms for maker-spaces. Two effective ways to promote innovation in maker-space are outlined: first, preventing interventions from external resource providers; second, building an inclusive culture of trial and error.